MUTATION INDUCED CONFORMATIONAL CHANGES IN MRNA THAT PREVENT OR INDUCE M6A METHYLATION AT DISTAL SITES - KHAN, Debjit; BLANKENBERG, Daniel; CUMBO, Fabio; FOX, Paul (2025)
The present invention relates to methods, kits, and compositions for testing a sample from a subject and determining: i) if said subject is A/A, A/C, or C/C at position 4444 in the Glutamyl-prolyl-tRNA synthetase 1 (EPRS1) gene or mRNA, and/or ii) if said subject expresses only the 1482T version, only the 1482P version, or both the 1482T and 1482P versions, of the EPRS1 protein; and/or iii) if said subject is m6A methylated or m6A unmethylated at A4355 and/or A4464 in said EPRS1 mRNA; and determining that the subject has hypomyelinating leukodystrophy (HLD) or other neurological condition. The present application also relates to a bioinformatic pipeline to assess if m6A-distal single-nucleotide-variations (m6Ad-SNV) affect methylation of DRACH sites. La présente invention concerne des procédés, des kits et des compositions permettant de tester un échantillon provenant d'un sujet et de déterminer : i) si ledit sujet est A/A, A/C ou C/C à la position 4444 dans le gène ou l'ARNm de glutamyl-prolyl-ARNt synthétase 1 (EPRS1), et/ou ii) si ledit sujet exprime uniquement la version 1482T, uniquement la version 1482P, ou les deux versions 1482T et 1482P, de la protéine EPRS1 ; et/ou iii) si ledit sujet est m6A méthylé ou m6A non méthylé à A4355 et/ou A4464 dans ledit ARNm d'EPRS1 ; et déterminer que le sujet est atteint d'une leucodystrophie hypomyante (HLD) ou d'une autre condition neurologique. La présente demande concerne également un pipeline bioinformatique pour évaluer si des variations mononucléotidiques distales m6A (m6Ad-SNV) affectent la méthylation de sites DRACH.